Barriers and facilitators for HIV rapid testing among transgender women and gay and other men who have sex with men in Brazil: A scoping review - Lidiane da Silveira Gouvea Toledo; Paloma Palmieri; Gizele da Rocha Ribeiro; Adriano da Silva; Francisco Inácio Bastos (Global Public Health)
Transgender women (TGW) and men who have sex with other men (MSM) often encounter disparities in accessing HIV testing, leading to delayed diagnoses and worse prognoses. We analysed barriers and facilitators for accessing HIV rapid testing by TGW and MSM in Brazil, 2004-2023. Citations were included whether the study population consisted of individuals aged ≥18y old, and studies addressed HIV testing and have been conducted in Brazil. The study protocol was based on Joanna Briggs’ recommendations for scoping reviews. We included 11 studies on TGW and 17 on MSM. The belief that one is not at risk of contracting HIV infection, fear expressed in different ways (e.g. lack of confidentiality) and younger age were the main barriers. Feeling at risk for HIV infection, curiosity, and favourable characteristics of the setting where the testing takes place were cited as the main facilitators. Barriers and facilitators specifically for HIV self-testing included, respectively, concerns about conducting the test alone vs. autonomy/flexibility. Brazil is unlikely to achieve the UN’ 95-95-95 goal without minimising testing disparities. Combating prejudice against TGW and MSM in testing settings, along with educational campaigns and transparent protocols to ensure confidentiality, can help increase HIV testing among these populations.